2019
DOI: 10.1557/mrs.2019.178
|View full text |Cite
|
Sign up to set email alerts
|

Enabling sustainable transportation through joining of dissimilar lightweight materials

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The search for less-polluting or zeropolluting transportation is seen among developing countries, especially in India, due to customer demand and rising environmental problems. Kleinbaum et al (2019) argued that by K 51,11 reducing the mass of a vehicle by 10%, vehicle fuel economy could increase by 6-8% and reduce emissions. Limiting private cars, encouraging non-motorized zones and creating pedestrian walkways are progressive methods to advance sustainable transportation.…”
Section: Enablers Of Sustainable Transportationmentioning
confidence: 99%
“…The search for less-polluting or zeropolluting transportation is seen among developing countries, especially in India, due to customer demand and rising environmental problems. Kleinbaum et al (2019) argued that by K 51,11 reducing the mass of a vehicle by 10%, vehicle fuel economy could increase by 6-8% and reduce emissions. Limiting private cars, encouraging non-motorized zones and creating pedestrian walkways are progressive methods to advance sustainable transportation.…”
Section: Enablers Of Sustainable Transportationmentioning
confidence: 99%
“…One commonly used strategy to achieve higher fuel efficiency is weight reduction in vehicle architectures by replacing metal parts with ones made of plastic. According to a recent study, 2 in on-highway passenger vehicles, a 10% weight reduction leads to an improvement in fuel economy of between 6 and 8%. Furthermore, it was reported that a 20% weight reduction was achieved for the Boeing 787 aircraft by incorporating 50% carbon fiber composite by weight instead of aluminum, which resulted in a 10–12% improvement in fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Low-density alloys such as aluminium introduce weight savings. At the same time, the implementation of advanced high-strength steels with their high alloying additions makes them desirable for their strength and ductility [1,2]. Nevertheless, implementing different material combinations, such as forming brittle intermetallic compounds, brings challenges.…”
Section: Introductionmentioning
confidence: 99%